Prevalence, incidence, and season distribution of MOG antibody-associated disease in the province of Verona, Italy - Orlandi, Riccardo; Mariotto, Sara; Gajofatto, Alberto (Multiple sclerosis and related disorders, 2022)
•MOGAD incidence and prevalence are still unclear.•We report incidence and prevalence of MOGAD in Verona province, Italy.•Prevalence-incidence lower than MS, higher than NMOSD with AQP4-IgG in Caucasians.•More frequent disease onset in autumn-winter period. Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) is a demyelinating disorder of the central nervous system whose epidemiological features are still unclear. We report current prevalence and incidence rates of MOGAD in the population of Verona province, Italy, and the seasonal distribution of disease onset. MOGAD patients residing in Verona province were included through the consultation of a database from our Neuropathology Laboratory. Provincial prevalence was determined on 2021/1/1 (resident population: 922,291 people) and incidence rates between 2016/1/1 and 2021/1/1 were calculated from all cases, divided by the total number of person-years at risk. We also examined the distribution of attacks by month and season. We included 23 prevalent MOGAD cases (13 females), with a median age at onset of 36 years (range 5–69). Prevalence rate was 2.5/100,000 (95% CI 1.7–3.7). 22 incident cases were collected, with an incidence rate of 4.8/million person-years (95% CI 3.1–7.2). Among the 23 prevalent patients, disease onset was more frequent in December (4 cases), February, May, and September (3 cases/month), with a global autumn-winter predominance (September-February) of 15 cases (65%), irrespective of the clinical manifestation. This is the first study on an Italian population to report MOGAD prevalence and incidence rates; they are higher than the estimates for aquaporin-4-seropositive neuromyelitis optica spectrum disorder in the Caucasian population, but far lower than Multiple Sclerosis. An autumn-winter predominance of disease onset is suggested, and it could be related to environmental factors that should be ascertained, although validation in larger cohorts is mandatory.